PELATIHAN APARATUR DESA TERKAIT PENGELOLAAN KEUANGAN DESA: UPAYA PENINGKATAN AKUNTABILITAS DAN TRANSPARANSI DESA - Christina Tri Setyorini; Dewi Susilowati; Yusriyati Nur Farida; Wita Ramadhanti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
This mentoring activity is based on the existence of the phenomenon of village officials who are embroiled in legal cases. Misinterpretation of Villages Law No. 6 of 2014 and Village Financial Management Permendagri No. 11 of 2014 resulted in numerous irregularities in village financial management. With so many legal cases, many village officials are hesitant to use village funds because they do not know how to manage them. This training was designed to improve village officials' understanding of how to manage village finances in accordance with applicable regulations. The training was enthusiastically attended by 42 village officials from various villages in the Cilongok District. Based on the results of the training conducted by administering pre-test and post-test, it is clear that training can improve village officials' understanding and has an increasing trend value between before and after training in village financial management. This demonstrates that the training is very effective in increasing the village apparatus's knowledge and understanding of village financial management, thereby increasing the absorption of the allocated village fund budget.